Vegetation response to cattle grazing in the Ethiopian highlands - Mwendera, E.J.; Mohamed-Saleem, M.A.; Woldu, Z. (Elsevier, 1997)
The effect of grazing cattle on vegetation was studied on a natural pasture during the rainy and dry seasons of 1995 in the Ethiopian highlands. The study used 0.01 ha plots, established on 0-4 percent and 4-8 percent slopes located close to each other at Debre Zeit research station, 50 km South of Addis Ababa. The grazing regimes were: light grazing stocked at 0.6 animal-unit-mouth per hectare (AUM ha-1); moderate grazing stocked at 1.8 AUH\M ha-1; heavy grazing stocked at 3.0 AUM ha-1; very heavy grazing stocked at 4.2 AUM ha-1; very heavy grazing on ploughed pasture stocked at 4.2 AUM ha-1; and a control of `no grazing'. Heavy grazing significantly reduced vegetative cover and biomass yields, especially on steeper slopes. Light to heavy grazing did not affect the botanical composition of the vegetation at both sites, but very heavy grazing resulted in species normally less preferred by animals dominating the botanical composition. Grazing did not have significant effect on ground vegetative cover on the 0-4 percent slope except at very heavy grazing pressure, but on the 4-8 percent slope even moderate grazing significantly reduced vegetative cover. Light to moderate grazing at the beginning of the dry period enhanced plant biomass productivity, while any grazing reduced plant productivity during the periods of reduced growth. Species richness increased with increasing grazing pressure compared with no grazing, but decreased sharply at very heavy grazing pressure. It is concluded that there is need for developing `slope and time specific' grazing management practices, and to assess short and long term effects of grazing and trampling on vegetation.